2003
DOI: 10.1186/bcr585
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory breast cancer: Vasculogenic mimicry and its hemodynamics of an inflammatory breast cancer xenograft model

Abstract: 136 EC = endothelial cell; IBC = inflammatory breast cancer; MRA = magnetic resonance angiography; VEGF = vascular endothelial growth factor; VM = vasculogenic mimicry. Breast Cancer Research Vol 5 No 3 Shirakawa et al. IntroductionGrowth, proliferation, and metastasis of breast cancer, and of most other tumors, have been thought to be angiogenesis-dependent processes [1]. However, a non-angiogenesis-dependent pathway, in which tumors can feed themselves using alternative pathways, has also been reported [2][3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
182
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(192 citation statements)
references
References 6 publications
(4 reference statements)
9
182
0
1
Order By: Relevance
“…Shirakawa and colleagues, using in vivo models of breast carcinoma, have demonstrated that aggressive breast tumors portray vasculogenic mimicry (without endothelial cells or central necrosis) that connects to angiogenic vessels at the tumor periphery. 5 In contrast, …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Shirakawa and colleagues, using in vivo models of breast carcinoma, have demonstrated that aggressive breast tumors portray vasculogenic mimicry (without endothelial cells or central necrosis) that connects to angiogenic vessels at the tumor periphery. 5 In contrast, …”
Section: Discussionmentioning
confidence: 95%
“…We and others have proposed that tumors, including ovarian carcinoma, may develop vascularization through angiogenesis as well as alternative pathways such as vasculogenic mimicry and mosaic vessels. [2][3][4][5][6] We have previously demonstrated that aggressive ovarian cancer cells, but not normal ovarian surface epithelial cells, are able to form vasculogenic-like networks in three-dimensional cultures, with concomitant expression of vascular-associated cell markers. 2 In addition, we have demonstrated that tumor cell-lined vasculature can be detected in aggressive cancers in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also have shown that some aggressive tumor cells can generate vessel-like channels, i.e., vasculogenic mimicry in the absence of endothelial cells (Shirakawa et al 2002, Su et al 2007), thus providing another pathway for tumor perfusion independent of angiogenesis (Folberg et al 2000). Su et al (2007) reported that the human ovarian cancer cell line SKOV3.ip1 may express some endothelium-specific markers after vasculogenic mimicry in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…VM has been reported in inflammatory breast cancer (6), prostate cancer (7), invasive ovarian cancer (8), sarcoma (9), and astrocytoma (10). VM is also involved in the invasion and metastasis of malignant tumors (6,7,11) and has been associated with poor prognosis in melanoma and sarcomas (8,9).…”
Section: Introductionmentioning
confidence: 99%